2016
DOI: 10.1177/2156587215621462
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and Alternative Medicines

Abstract: Prevalence of complementary and alternative medicines is increasing specially in patients with chronic diseases. Therefore, based on the high prevalence of chronic disorders, the present study aimed to determine complementary and alternative medicine usage frequency and its determinant factors. This was a cross-sectional study. Five hundred clients participated in the study by using convenience sampling. A 2-part questionnaire (including demographic form and researcher-created questionnaire) was used for study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 22 publications
0
12
1
Order By: Relevance
“…This study showed some differences with Ghaed et al results that reported the most common reason for the use of complementary alternative medicine was the common cold in one-third of cases [20]. Similarly, Sheikhrabori et al showed that the most common therapeutic options were medicinal plants used by 85% of the participants [21].…”
Section: Discussioncontrasting
confidence: 66%
“…This study showed some differences with Ghaed et al results that reported the most common reason for the use of complementary alternative medicine was the common cold in one-third of cases [20]. Similarly, Sheikhrabori et al showed that the most common therapeutic options were medicinal plants used by 85% of the participants [21].…”
Section: Discussioncontrasting
confidence: 66%
“…Likewise, in some places, complementary medicine is the only source of alternative medicine to conventional. On the other hand, one study showed that many people opt for this type of alternative medicine in the face of dissatisfaction with conventional medicine [74][75][76]. Similarly, a study by Santiváñez-Acosta [77] found that 19.5% of residents (out of 179 respondents) in Peru's Ucayali region made use of herbal medicine throughout the year.…”
Section: Discussionmentioning
confidence: 99%
“…Also, its reliability was determined by a pilot study on 30 people of the target population who used CAM. The Cronbach's α was reported as 0.77 28 . In another study, Dehghan et al did some minor revisions on the questionnaire; They reported the content validity index of the questionnaire as 0.96, and for the internal consistency Cronbach's α coefficient was 0.85 25 .…”
Section: Methodsmentioning
confidence: 99%